A contribuição da RPPN para a preservação da biodiversidade: uma análise jurídica da RPPN da UPF - Ribeiro, Kenedy (2024)
Amid the frequent increase in natural disasters, it is necessary to intensify the fight against the overexploitation of forest and water resources, enforcing current legislation. It is also necessary for more information to be made available to society about sustainable development alternatives. In this sense, it is justified to discuss the benefits of creating and preserving Private Natural Heritage Reserves (RPPN). In this context, the general objective of this work is to address environmental legislative developments, with regard to water and forestry resources and the recognition and protection of the environment, demonstrating that natural resources are finite. In particular, the need to protect and preserve the sources of rivers is revealed, since, without water, there will be no humanity on Earth. The specific objective of the work is to address the importance of the RPPN at the University of Passo Fundo (UPF), not only for university students, but for the entire society of Passo Fundo and surrounding areas, aiming for the common good. It is concluded that the need to preserve the remaining natural resources becomes increasingly urgent, as it is “everyone’s duty to take care of the environment”.